ANALISIS KLASTER WILAYAH PADA PENGELOLAAN SAMPAH MELALUI BANK SAMPAH DI KALIMANTAN MENGGUNAKAN FUZZY K-MEANS UNTUK PENGUATAN KEBIJAKAN LINGKUNGAN - Rosady, Erzha Nafilah; Rizqi, Zafyra Nur; Nur, Muhammad Dafiq; Sinambela, Johannes Martin; Sari, Surya Puspita; Effendi, Magdalena (BPS Kalimantan Timur, 2025)
The increase in waste generation in Kalimantan, along with population growth and economic activity, has become a complex environmental issue. The disparity in management capacity among regions has led to differences in the effectiveness of waste management systems, particularly in the implementation of waste banks as a form of community-based management. This study aims to cluster regencies/cities in Kalimantan based on waste management characteristics using the Fuzzy K-Means method to obtain a spatial mapping that supports the formulation of fairer and more efficient waste management policies. Secondary data were obtained from the National Waste Management Information System (SIPSN) and the Central Statistics Agency (BPS), covering variables such as waste generation, managed waste volume, land area, and population. The analysis results show that the optimal number of clusters is two (2): one cluster representing regions with high waste management performance dominated by major cities such as Balikpapan and Banjarmasin, and another cluster representing regions with low management performance due to limited infrastructure. These findings highlight spatial disparities in the effectiveness of waste bank programs across Kalimantan. The clustering results are expected to serve as a foundation for local governments in developing strategies to strengthen waste management policies, particularly through the implementation of the national program “1 RW 1 Waste Bank” and the adoption of sustainable circular economy principles.